YhjX Regulates the Growth of Escherichia coli in the Presence of a Subinhibitory Concentration of Gentamicin and Mediates the Adaptive Resistance to Gentamicin - Zhou, Shuqin; Zhuang, Yijing; Zhu, Xiaojuan; Yao, Fen; Li, Haiyan; Li, Huifang; Zou, Xiaoguang; Wu, Jianhua; Zhou, Huifang; Nuer, Gulibaier; Huang, Yuanchun; Li, Shao; et al. (Frontiers in Microbiology, 2019)
The mechanisms of adaptive resistance of Escherichia coli to aminoglycosides remain unclear. Our RNA-Seq study found that expression of yhjX was markedly upregulated during initial exposure to subinhibitory concentrations of gentamicin. The expression of yhjX was then downregulated dramatically during a second exposure to gentamicin compared to the first exposure. YhjX encodes a putative transporter of the major facilitator superfamily, which is known to be the sole target of the YpdA/YpdB two-component system, the expression of which is highly and specifically induced by pyruvate. To investigate the effect of yhjX on the adaptive resistance of E. coli, in the present study, we constructed yhjX deletion and complemented strains of E. coli ATCC25922. Changes in extracellular pyruvate levels of wide-type and yhjX mutant were measured to determine whether YhjX functions as a pyruvate transporter. The results showed that yhjX deletion improved the growth of E. coli in medium containing subinhibitory concentrations of gentamicin. The yhjX deletion mutant did not exhibit adaptive resistance to subinhibitory concentrations of gentamicin. YhjX might not function as a pyruvate efflux pump in E. coli but was associated with the decrease following a sharp increase in the extracellular pyruvate level. Our findings indicate that yhjX regulates the growth of E. coli in the presence of a subinhibitory concentration of gentamicin and mediates the adaptive resistance to gentamicin.